FAKTOR INTERNAL DAN EKSTERNAL TERHADAP DAYA TERIMA IBU HAMIL PADA PEMBERIAN MAKANAN TAMBAHAN BERBASIS PANGAN LOKAL - Arami, Ayu; Fitriani; Farisni, Teungku Nih (Bina Generasi : Jurnal Kesehatan, 2025)
Backround : The problem of malnutrition in pregnant women continues to attract attention. One of them is the risk of chronic energy deficiency in pregnant women. Chronic energy deficiency in pregnant women is a problem that involves reduced protein and energy intake during pregnancy and can cause health problems for the mother and fetus. Objective : To determine the influence of internal and external factors on the acceptance of pregnant women when providing additional food based on local food as an effort to reduce KEK in the work area of ​​the Cot Kuta District Health Center, Nagan Raya. Method : in this research is a quantitative approach with a non-parametric analytical descriptive research type. Results : There is an influence of internal factors, namely the nutritional knowledge variable with (P value = 0.04), external factors, namely the food texture variable with (P Value = 0.02), food taste with (P value = 0.02), food taste with (P value = 0.04). P Value = 0.05), food variety with (P Value = 0.04) and food aroma with (P Value = 0.04). Meanwhile, the factors that have no influence are internal factors, namely education with (P Value = 0.09) and eating habits with (P Value = 0.76). Conclusion : There is an influence of internal and external factors on the acceptance of pregnant women through food waste during supplementary feeding. "There is an influence between internal factors from the variable nutritional knowledge on the acceptability of pregnant women, then there is another influence from external factors, namely the variables of food taste, texture, variety and aroma of food on the acceptability of pregnant women."